POLICY EVALUATION: IMPACT OF IMPORTATION INCOME TAX INCENTIVE - Rahadian Lungun (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This study aims to evaluate the effectiveness of the Income Tax Incentive on Imports in maintaining the productivity of construction taxpayers in the Kota Bekasi Medium Tax Office during the Pandemic. It uses a positivism approach with a quantitative method. This method adopts the difference-in-differences analysis. Such a method measures the average treatment effect of the construction taxpayers’ productivity before and after the implementation. The construction sector is selected as the research object since it becomes the Government’s most targeted sector under the incentive policy. Meanwhile, this study selected the Kota Bekasi Medium Tax Office because it faced the lowest decline during the Pandemic. The study concludes that the Income Tax Incentive on Imports is insignificantly effective in maintaining the Total Factor Productivity of construction taxpayers in the Kota Bekasi Medium Tax Office. This insignificant effectiveness is attributed to the low utilisation rate, with 96% of construction taxpayers not utilising the incentive. The low utilisation is due to a lack of interest from construction taxpayers and the limited value of the tax incentive. However, such an incentive could effectively maintain the Total Factor Productivity of the construction taxpayers utilising the incentive. Therefore, this study recommends that the Government monitor utilisation levels and promptly assess the tax incentive's effectiveness before considering its re-implementation during construction taxpayers’ productivity decline.